Informe de acompañamiento para la integración de la perspectiva de género en el trabajo con parcelas de evaluación de variedades biofortificadas - Chavarro, Monica Juliana (2023)
In the context of the implementation of a biofortified rice plot in the municipality of Zapatero, Bolivar, the need was identified to approach the experience from a gender and social inclusion perspective, since it was a group of women who were in charge of its implementation. During a visit to the community, a workshop and observations were carried out to analyse gender dynamics, roles in rice production and the effectiveness of technical assistance. The results showed women’s participation in various agricultural activities and no change in the gender gap in the community. Recommendations were also made regarding technical assistance and the importance of a gender and social inclusion approach.